PENGEMBANGAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI PIXELLAB DALAM MENULIS CERITA FANTASI KELAS VII: PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI PIXELLAB DALAM MENULIS CERITA FANTASI KELAS VII - Nassarudin, Muhammad; Arlin, Febyana; Rustam (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to develop application-based learning media in writing fantasy stories for class VII. The type of research and development that the author uses in this research is the Research and Development method and development. Research and Development is research used to produce a particular product and test the effectiveness of the product to be researched. The results of observations of the learning process using the Pixellab application in writing fantasy stories for class VII show that learning to write fantasy stories shows that students' activities are effective, creative, active and fun.